Comparative study of the laxative effects of konjac oligosaccharides and konjac glucomannan on loperamide-induced constipation in rats. Issue 17 (21st July 2021) - Hu, Mengmeng; Fang, Changqian; Liu, Youqian; Gao, Meng; Zhang, Dongjian; Shi, Gaofeng; Yin, Zhiqi; Zheng, Rendong; Zhang, Jian
Abstract : Dietary fiber is the basic therapeutic method to relieve the symptoms of chronic constipation. Abstract : Dietary fiber is the basic therapeutic method to relieve the symptoms of chronic constipation. The aim of this study was to compare the laxative effect of konjac glucomannan (KGM) and konjac oligosaccharides (KOS) on constipated rats. KGM and KOS were administered to loperamide-induced constipated rats at dosages of 100 mg per kg bw and 400 mg per kg bw for 15 days. Feces were collected to evaluate the defecation function. X-ray imaging and an electrophysiological system were used to determine gastrointestinal (GI) motility. Immunohistochemistry and western blotting were used to measure the protein levels. Magnetic resonance imaging (MRI) was performed to assess flatulence. Our results demonstrated that low-dose KOS (L-KOS) exerted the best laxative effect. Compared to the normal control (NC) group, the fecal number in the L-KOS group increased by 39.4%, and the fecal weight significantly increased by 31.9% which was higher than those in the low-dose KGM (L-KGM) and high-dose KGM (H-KGM) groups. The fecal moisture content and transit scores were significantly increased only in the L-KOS group. Meanwhile, less GI gas was produced by KOS. Additionally, further investigations suggested that KOS could upregulate the protein expression of stem cell factors (SCF)/c-kit, and significantly promoted the secretion of mucus. In conclusion, compared to KGM, KOS had a conspicuous laxative effect especially at a low dosage. The potential laxative mechanisms of KOS probably are regulating the SCF/c-kit signalling pathway and increasing mucus secretion. These findings indicated that as a kind of functional oligosaccharide, KOS is more conducive to alleviating constipation compared to polysaccharides.